Benefit‐risk assessment for sofosbuvir/velpatasvir/voxilaprevir based on patient population and hepatitis C virus genotype: U. S. Food and Drug Administration's evaluation. Issue 2 (1st January 2018) - Struble, Kimberly; Chan‐Tack, Kirk; Qi, Karen; Naeger, Lisa K.; Birnkrant, Debra
Abstract : On July 18, 2017, the U.S. Food and Drug Administration (FDA) approved sofosbuvir/velpatasvir/voxilaprevir (SOF/VEL/VOX) (Vosevi) fixed‐dose combination (FDC), an interferon‐free, complete regimen for adult patients with chronic hepatitis C virus (HCV) infection without cirrhosis or with compensated cirrhosis (Child‐Pugh A) who have: genotype 1, 2, 3, 4, 5, or 6 infection and have previously been treated with an HCV regimen containing a nonstructural protein 5A (NS5A) inhibitor; and genotype 1a or 3 infection and have previously been treated with an HCV regimen containing sofosbuvir without an NS5A inhibitor. Approval was based on an acceptable safety profile and high sustained virological response rates 12 weeks after the end of treatment (SVR12) in two phase 3 clinical trials in subjects previously treated with a direct‐acting antiviral (DAA) regimen. In POLARIS‐1, 96% of SOF/VEL/VOX‐treated subjects achieved SVR12. In POLARIS‐4, 98% of SOF/VEL/VOX‐treated subjects achieved SVR12. A key and challenging question in evaluating the data was determining the contribution of VOX to SOF/VEL and how this differed depending on the genotype and patient population. In this article, we provide our perspective on the issues considered in making these determinations, especially regarding the POLARIS‐4 data in subjects who have previously been treated with a chronic HCV regimen containing sofosbuvir without an NS5A inhibitor. Conclusion: We seek to provide context as to why a broad indication was given for NS5A inhibitor‐experienced patients (HCV genotypes 1‐6) while the indication for NS5A inhibitor‐ naïve patients was limited to HCV genotypes 1a and 3 only. (Hepatology 2018;67:482‐491).